Challenges in Cross-border E-commerce in the European Union - Kalinić, Zoran; Ranković, Vladimir; Kalinić, Ljubina (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Electronic commerce (e-commerce), usually defined as trade conducted over computer networks, has attracted considerable attention for decades. Тhe paper presents the current state of development of retail e-commerce in the European Union, with particular analysis of development of cross-border online trade. Despite its considerable effort, the European Union is still far from an integrated market, as online shoppers still prefer domestic markets to other EU markets. The focus of the paper is on the main challenges of cross-border B2C e-commerce, i.e. online purchases of individual EU consumers made in other EU countries. Some important barriers to the establishment of a fully-integrated digital market in the European Union, including issues related to logistics and delivery, language and location, legal and tax regulation and geo-blocking, are addressed in detail. Finally, ongoing activities to reduce the influence of these obstacles are presented.